2020
DOI: 10.1093/mnras/staa203
|View full text |Cite
|
Sign up to set email alerts
|

Wind collision and accretion simulations of the massive binary system HD 166734

Abstract: We run hydrodynamic simulations which follow the colliding winds structure of the massive binary system HD 166734 along its binary orbit, and show that close to periastron passage the secondary wind is suppressed and the secondary accretes mass from the primary wind. The system consists two blue supergiants with masses of M 1 ≈ 39.5 M ⊙ and M 2 ≈ 30.5 M ⊙ , on a P ≃ 34.538 days orbit with eccentricity of e ≈ 0.618. This close O-O binary with high eccentricity is observed through its orbit in the Xrays, where i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
2
2
0
Order By: Relevance
“…Our later simulations in Kashi (2017) included radiation pressure and showed that radiative breaking cannot prevent the accretion, by that confirming the theoretical prediction given by Kashi & Soker (2009c). These simulations in Kashi (2017) are also the first that solve the stars not as point sources but as approximated spheres, allowing directional analysis for accretion. In Kashi (2019) we studied four methods for treating accretion and the response of the accretor to the incoming wind, and found a numerical implementation for treating accretion and wind outflow simultaneously.…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our later simulations in Kashi (2017) included radiation pressure and showed that radiative breaking cannot prevent the accretion, by that confirming the theoretical prediction given by Kashi & Soker (2009c). These simulations in Kashi (2017) are also the first that solve the stars not as point sources but as approximated spheres, allowing directional analysis for accretion. In Kashi (2019) we studied four methods for treating accretion and the response of the accretor to the incoming wind, and found a numerical implementation for treating accretion and wind outflow simultaneously.…”
Section: Introductionsupporting
confidence: 88%
“…Those clumps flow towards the secondary but cannot be decelerated by the ram pressure of the secondary wind and hit the regions from where the secondary wind is launched. Our later simulations in Kashi (2017) included radiation pressure and showed that radiative breaking cannot prevent the accretion, by that confirming the theoretical prediction given by Kashi & Soker (2009c). These simulations in Kashi (2017) are also the first that solve the stars not as point sources but as approximated spheres, allowing directional analysis for accretion.…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…Hydrodynamical wind-wind collision studies show that when the wind momentum of one of the stars is significantly larger than that of its companion, a fraction of the shocked wind is accreted (Matsuda et al 1992;Ruffert & Arnett 1994;Nagae et al 2004). Under stationary conditions, the accretion rate is (probably) not sufficient to affect the secondary, but if the incoming stellar wind evolves over time becoming denser and slower, then the numerical simulations find that high density clumps produced by the instabilities in the shocks will fall onto the secondary star (Kashi 2020), potentially leading to non-negligible accretion rates. If such a phenomenon occurred in 1992-1994, the violent expulsion of the material accreted onto Star B could have been responsible for the transitory B1.5Ia + spectrum observed in 1994 and the rapid spectral evolution of the system over the following two years.…”
Section: The 1993-1994 Sudden Eruptionsmentioning
confidence: 99%